The poetic image and its function in the poetry of Javad Al-Hattab (Journal of the College of Basic Education, 2023)
Everything has an essence, and the essence of poetry is its images, so that we see that the poets, both old and new, were mastering in creating images to highlight their poetic power, taking the core of their audience and their hearing. In fact, the writer, especially the contemporary, after he and his people lived in difficult circumstances, deviated with his poetry from the rivers of his country so that the hands of the arrogant would not attack him, and he also seeks, through his poetic art, to send a message to the sons of his people to awaken the determination against persecution, i.e. the two sources of it.At the forefront of these poets standing against injustice is the poet Javad Al-Hattab, who resisted the American occupation and his accomplices, as he spent his life uttering his resounding cry, rejecting their arbitrariness and criminality against his people. Moreover, through his research, the researcher intends to stop at the poetic image in the poems of the poet Al-Hattab in order to delve into it and extract its most important semantic functions; The researcher revealed that all the images of this poet’s poetry reflect what he calls for the necessity of resisting the occupation; It was also found that the poet sought, through the picture, to embody his thoughts, expressing his emotions and feelings.Finally, it became clear that his poetic image served some functions, including the provocative reporting function, the informative impactful function, and the psychological function that indicates what the poet feels about what is happening in his country of sorrows and joys.